Temporal Gradient During Famous Face Naming is Associated with Lower Cerebral Blood Flow and Gray Matter Volume in Aging - Hays, Chelsea C. (Neuropsychologia, 2017)
OBJECTIVE: Evidence suggests that famous face naming may be a cognitive ability especially sensitive to the early pathological processes of Alzheimer’s disease (AD) and that those at risk for AD may demonstrate a Ribot temporal gradient (RTG), characterized by better performance for naming remote famous faces than for naming recent famous faces. Reductions in cerebral blood flow (CBF) and gray matter volume (GMV) have been implicated in the neuropathological cascade of AD and show utility as biomarkers of AD risk. We examined whether a RTG during famous face naming was associated with lower CBF and/or GMV among a group of cognitively normal older adults. METHODS: Voxel-wise independent samples t-tests were employed to contrast resting CBF values between those who exhibited a RTG (RTG+) during a famous face naming task and those who did not (RTG−) among a sample of 52 cognitively normal older adults (25 RTG−, 27 RTG+; mean age=73). Groups were also compared on GMV using a voxel-wise general linear model. RESULTS: Significant group differences in CBF and GMV were found, whereby the RTG+ group demonstrated reduced CBF and GMV within medial temporal lobe regions (hippocampus, parahippocampal gyrus), relative to the RTG− group. CONCLUSIONS: This represents the first study to show that cognitively intact older adults who demonstrate a RTG during famous face naming exhibit vascular dysregulation and structural changes similar to that seen in AD risk. Findings suggest that famous face naming ability may be particularly sensitive to the very early brain changes associated with AD.